Analisis Input Output Sektor Pertanian di Indonesia - Hani Perwitasari; Irham Irham; Jamhari Jamhari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
The purpose of this research are (1) to identify changes in the structure of Indonesia’s economi, (2) to identifty backward linkage and forward linkage between agriculture sector eith other sctors in economic structure of Indonesia, (3) to know the multiplier effect of output, income, employment and grows value added of agriculture sector. The research analyzed Input-Output data, the domestic transaction based on producer price, that in classified 66 sectors published by the Cnetral Statistics Agency (BPS) uidng Input-Output Analysis.These result indicate that ini 1975 until 2008 the structure of Indonesia’s economy has changed towards industrialization. Backward linkage and forward linkage between the agriculture sectora are under the average backward linkage and the forward linkage of economy all sector in Indonesia. Multiplier effect to output, income, employment in the agricultural sector are the average of output multiplier effect income, employment sectors of the economy throughout Indonesia but the gross value added in above-average gross value added multiplier effects throught the economy of Indonesia.